DIRECTIONS FOR THE DEVELOPMENT OF GREEN INSURANCE TYPES: SCIENTIFIC-THEORETICAL AND PRACTICAL APPROACH (Лучшие интеллектуальные исследования, 2025)
Annotation. The article analyzes the scientific and theoretical foundations of types of green insurance within the green economy, international practice, as well as the possibilities of implementing and developing these types of services in the context of Uzbekistan. It also puts forward existing problems and practical proposals for their elimination.